Ancient Jewish magic: a history - Bohak, Gideon (Cambridge Univ. Press, 2008)
Jewish magic : a contradiction in terms? -- Jewish magic in the Second Temple period -- Jewish magic in late antiquity -- The "insider" evidence -- Non-Jewish elements in late-antique jewish magic -- How "Jewish" was ancient Jewish magic? -- Magic and magicians in rabbinic literature